TRANSPARANSI, AKUNTABILITAS DAN PARTISIPASI DALAM PENGELOLAAN APB NAGARI DI KECAMATAN KAMANG MAGEK - Mercya Vaguita; Hilda Oktri Yeni (Ensiklopedia Social Review, 2021)
The purpose of this study was to find out the management of local government budget in Kamang Magek Subdistrict, Agam Regency. This research is a descriptive analysis using a qualitative approach that uses primary data and secondary data. The technique of collecting data is in the form of field research by means of interviews, focus group discussions (FGD), and documentation studies with valid and accurate sources. The results of the study showed that the management of local government budget has not fully run well this is because there are still obstacles faced in accordance with Permendagri Number 113 of 2014 and Perbub Agam Number 8 of 2017. (1) Implementation of the principle of transparency consists of indicators, namely openness in meetings, openness of information, openness of procedures, and openness in accepting community participation. (2) Implementation of the principle of participation consists of indicators, namely the existence of active public participation, the existence of regulations that provide a place for community control, and the presence of proactive attitudes of regional governments in the budgeting process. (3) Implementation of the principle of accountability consists of indicators, namely the existence of honesty and legal accountability, the existence of process accountability, the existence of program accountability, and the existence of policy accountability